Advertising and promotion in the economic reactivation of the markets of the city of Riobamba - Trujillo Chávez , Hugo Santiago; Moyano Vallejo, Hernán Patricio (mktDESCUBRE, 2023)
Advertising is a commercial communication strategy that encourages people to consume a product or service, becoming a form of communication between the establishment and its customers; An important complement is a promotion in the establishments that will allow the increase of a positive perception towards a certain product and therefore towards the brand. The objective of the research was to determine the level of incidence of advertising and promotion in the economic reactivation of the markets of the city of Riobamba, for which the sample considered for the study was 417 establishments. The results show that the commercial premises of the markets consider advertising and promotion as very important for their economic reactivation and apply communication strategies such as promotion and customer service, publicizing their businesses on their own premises as well as on social networks and considered as limitations for the application of the strategies are the budget, ignorance, and lack of support from the authorities.